Development of the Effect of Video Assistant Referee Application on Football Parameters - Buyukcelebi, Hakan; Duz, Serkan; Acak, Mahmut; Nalbant, Umut; Svatora, Karel; Gabrys, Tomasz; Karayigit, Raci (Mdpi, 2022)
The Video Assistant Referee (VAR) application is a technological development that gives referees the chance to review their critical decisions. The current study aimed to determine the effect of the VAR system in international football organizations on the game over the years. The sample of the study consists of 115 football matches, specifically 64 matches played in the 2018 FIFA World Cup and 51 matches played in the 2020 European Football Championship. In the competitions handled, the number of goals, the number of yellow cards, the number of red cards, the first half time, the second half time, the total match time, the number of penalties and the number of offsides were examined. The Mann-Whitney U test was used to compare two independent groups. As a result, in the 2020 European Football Championship, there was a decrease in the second half time (p = 0.01) and total match time (p = 0.01), and a significant increase in the number of offsides (p = 0.03) compared to the 2018 FIFA World Cup. On the other hand, there was no significant difference between the two tournaments in the variables of number of goals, number of yellow cards, number of red cards, half time and penalty shootout (p > 0.05). In light of the data obtained, it can be said that the effect of the VAR system on the spirit of the game will decrease as the share of the VAR system in the pauses during the competition decreases over the years. The data revealed in the study may be a clue to explaining why the effect of the VAR system on game dynamics and game spirit has decreased over the years. Therefore, the concerns of football stakeholders about the effects of the system on the game may gradually decrease with the arrangements made for VAR.
Keywords: football; match analysis; referee; performance analysis; soccer; video assistant referee